2023
DOI: 10.1002/wcc.828
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making factor interactions influencing climate migration: A systems‐based systematic review

Abstract: Global migration and mobility dynamics are expected to shift in the coming decades as a result of climate change. However, the extent to which migration is caused by climate hazards, in contrast or addition to other intervening factors, is a point of debate in literature. In this study, we conducted a systematic literature review to identify and consolidate factors which directly and indirectly influence climate change migration. In our review of the literature, we found a total of 21 economic, environmental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 93 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Despite human mobility being a product of a mix of choices and constraints at an individual level (Naser et al, 2023), the results of the analysis of human mobility perspectives revealed a (Kelman, 2020). In practice, Nabong et al (2023) identify around 20 economic, environmental, demographic, political, social and personal intervening decision-making factors that affect migration-related decisions within the context of climate change.…”
Section: Proposal Of a Theoretical-methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite human mobility being a product of a mix of choices and constraints at an individual level (Naser et al, 2023), the results of the analysis of human mobility perspectives revealed a (Kelman, 2020). In practice, Nabong et al (2023) identify around 20 economic, environmental, demographic, political, social and personal intervening decision-making factors that affect migration-related decisions within the context of climate change.…”
Section: Proposal Of a Theoretical-methodological Frameworkmentioning
confidence: 99%
“…De Sherbinin et al (2022) identify a general tendency of environment and climate-induced mobility to have limited engagement with existing theory (de Sherbinin et al , 2022), which might further feed general assumptions on how climate change and environmental degradation impact mobility-related decisions when populations are exposed to risks (Kelman, 2020). In practice, Nabong et al (2023) identify around 20 economic, environmental, demographic, political, social and personal intervening decision-making factors that affect migration-related decisions within the context of climate change.…”
Section: Proposal Of a Theoretical–methodological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In seeking alternative methods, network analysis 35 has gained momentum as an accepted practice to quantitatively identify leverage points based on CLDs 8 , 23 30 , 36 55 —for example in public health 24 , 38 , 45 , 50 , 52 , 53 , 55 . Here, 22 of the 29 papers that we identified that adopt this practice were published in 2021 (4 papers 23 , 25 , 37 , 50 ), 2022 (8 papers 27 , 28 , 43 45 , 47 , 49 , 52 ), and 2023 (10 papers to date 26 , 30 , 36 , 38 , 39 , 41 , 42 , 46 , 53 , 55 ). Network analysis seemingly has the potential to mathematically analyse a CLD, which in this context can be considered a network of factors, to systematically find which factors represent leverage points.…”
Section: Introductionmentioning
confidence: 99%
“…Currently in the literature relating to the development and analysis of CLDs, the term 'leverage point' tends to be used as referring to a factor within the CLD "in which change is likely to yield significant shifts elsewhere in the system" 23 . The key premise is that the system depicted in the CLD is producing undesirable system-level behaviour, and that there are central drivers in the system that could be influenced in such a way that this undesirable system-level behaviour is sustainably disrupted 8,[24][25][26][27][28][29][30] .…”
mentioning
confidence: 99%